Warming temperatures are impacting the hydrometeorological regime of Russian rivers in the zone of continuous permafrost. - Makarieva, Olga; Nesterova, Nataliia; Sherstyukov, Artem (PANGAEA, 2018)
Hydrometeorological data for two large Arctic rivers basins - the Yana and Indigirka, with both completely located within the continuous permafrost zone and which have long-term streamflow observations along the main rivers and their tributaries at smaller scales, are presented. The dataset contains mean and maximum daily monthly discharge for 22 hydrological gauges in the Yana and Indigirka River basins with catchment areas from 18.3 to 305 000 sq. km. Most of the gauges have hydrological data until 2014-2015. The median length of hydrological observations series is 62 years with minimum and maximum values reaching 36 and 80 years respectively. Additionally monthly air temperature and precipitations for 13 meteorological stations of the region for the period from 1957 to 2015 is presented. The data of mean monthly soil temperature at different depths at 3 stations for 1966-2015 period complement the dataset.
Monthly hydro-climate database for the Yana and Indigirka Rivers basins, Northern Eurasia